Feeding ecology, space use and habitat selection of elephants in two enclosed game reserves in the Eastern Cape Province, South Africa - Roux, Candice (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2006)
The development of small (<300 kmÂ²), private game reserves has become a trend, not only in the Eastern Cape Province, but also elsewhere in South Africa as a result of a shift in land use practise from agriculture to ecotourism. The resultant re-introduction of elephants to many of these reserves has lead to management concerns because of the limited research on small reserves regarding their impact on the vegetation. In this study I assessed the space use, habitat selection, diet and impact of two elephant populations on the vegetation in the Eastern Cape Province between February 2004 and March 2005. Home range sizes were calculated using the kernel utilization distribution method. Home range sizes for elephants on Kwandwe were significantly larger during summer than winter (p<0.05). There was no significant difference between the home range sizes of the herds and males within a season and during summer the elephants utilized about 75 % of the reserve and only 54 % during winter. On Shamwari, the herd utilized about 92 % of the reserve during summer and 83 % during winter; while the males utilized 76 % of the reserve. Core areas for both elephant populations shrank from summer to winter and were concentrated around the permanent water sources on each reserve. Habitat selection was assessed using Ï‡Â² tests and Bonferroni confidence intervals. On Kwandwe, there was a significant difference between observed and expected use of vegetation types (p<0.05) and karroid shrubland was strongly avoided by both herds during summer and winter. The preferred vegetation types of the males ranged from relatively open (short euphorbia thicket, bushclump karroid thicket and karroid shrubland) to completely open (old lands). On Shamwari, subtropical thicket, bontveld and montane grassland were avoided; while primary and secondary acacia thicket, riverine thicket and cultivated lands were preferred. The predominant vegetation type in the home ranges of herds on Kwandwe and Shamwari was subtropical thicket. The diet was assessed by direct observations over two seasons and dietary preferences were calculated. There was a significant difference in the frequency of occurrence of plants in the diet on the two reserves (p<0.05) and no significant effect of time of day or season (p>0.05). Seventeen woody plant species were utilized on Kwandwe and 23 species were utilized on Shamwari. Grass constituted a significantly greater percentage of the diet in summer than winter (p<0.05). Elephants on Kwandwe showed a selective preference for Ozoroa mucronata, Pappea capensis and Acacia karroo; while on Shamwari, A. karroo was selected. Transects were conducted in two different vegetation types on each reserve so as to assess the impact of elephant on the vegetation and damage scores were then calculated from these data. There was no significant effect of vegetation type or elephant density on mean damage scores in Kwandwe (p>0.05). Five hundred and seventy-eight plants were assessed in the subtropical thicket vegetation type and 225 plants were assessed in the savanna-type vegetation, with more than half the trees showing low levels of damage that could not only be attributed to elephants. Mean damage was highest for Portulacaria afra and Pappea capensis in subtropical thicket and for Rhus spp. in the savanna-type vegetation. On Shamwari, 408 plants were assessed in subtropical thicket and 215 in the savanna-type vegetation, with more than 70 % of trees showing low levels of damage. There was a significant effect of plant species and elephant density on the mean damage scores in subtropical thicket, with Aloe ferox showing more damage than the other plant species (p<0.01). In the savanna-type vegetation, A. karroo was the most severely damaged. Overall, damage was greater in the thicket vegetation type compared to the more open vegetation type on both reserves.
Keywords: Shamwari Game Reserve (South Africa); Kwandwe Game Reserve (South Africa); Elephants -- South Africa -- Eastern Cape; Elephants -- Ecology -- South Africa -- Eastern Cape; Elephants -- Feeding -- South Africa -- Eastern Cape; Elephants -- Nutrition -- South Africa -- Eastern Cape; Elephants -- Behavior -- South Africa -- Eastern Cape; Elephants -- Habitat -- South Africa -- Eastern Cape